Exploration Postpartum Sectio Caesarea with Ineffective Breastfeeding: A Case Report - Rizeki Dwi FIbriansari Fibriansari; Nurul Hayati; Sri Wahyuningsih; Nindi Bilih (D'Nursing and Health Journal (DNHJ), 2022)
Introduction: Problems often arise after section Caesarea such as pain in the incision area. Pain will cause the patient to delay breastfeeding from start. In addition, the psychological impact of post-section Caesarea patients is anxiety when giving breast milk, causing milk to not come out. This study reports the exploration of postpartum mothers with ineffective breastfeeding. Method: This method uses descriptive quantitative research through case reports. Participants were 2 post-section Caesarea patients on day 0 (Mrs. S and Mrs. M) who were treated at Lumajang Hospital, with lumbar anesthesia, had no history of infectious diseases, nipples did not protrude or flat, and were willing to be respondents with signed informed consent. Result: The results of the study on the third day, the patient Mrs. S said the milk came out smoothly, the nipples stood out, and the baby was able to suckle. Patient Mrs. M breastfeeds smoothly and the nipples are slightly protruding and the baby can suckle. Breast care using the Hoffman technique is an effective intervention to treat mothers with ineffective nursing problems due to flat nipples. Conclusion: Nursing problems are ineffective breastfeeding for patients seen from the condition of the patient's nipples and patient complaints, coupled with the Hoffman technique and other innovations so that nursing care provided can be resolved.